2020
DOI: 10.1021/acsenergylett.0c01236
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Crystalline and Shape Anisotropy on Electrochromic Modulation in Doped Semiconductor Nanocrystals

Abstract: Localized surface plasmon resonance (LSPR) modulation appearing in the near-infrared range in doped semiconductor nanocrystals enriches electrochromic performance. Although crystalline and shape anisotropies influence LSPR spectra, study of their impact on electrochromic modulation are lacking. Here, we study how crystalline anisotropy in hexagonal cesium-doped tungsten oxide nanorods and nanoplatelets affects essential metrics of electrochromic modulation-coloration efficiency (CE) and volumetric capacity-usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 46 publications
3
39
0
Order By: Relevance
“…Transition metal oxide nanocrystals have drawn considerable attention as candidate materials for electrochromic smart windows due to their rich tunability through structural control . By applying a colloidal approach, several structural features of the nanocrystals can be precisely controlled, including crystal phase, particle size, morphology, aliovalent dopant concentration, etc. At an atomic level, it was reported for WO 3– x bulk films and nanocrystals that the local structure of the Li insertion sites has an influence on their coloration efficiency and stability. ,, Moreover, it was shown that engineering the surface facets of WO 3– x nanocrystals by structural control can be used as a method to optimize several electrochromic properties .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition metal oxide nanocrystals have drawn considerable attention as candidate materials for electrochromic smart windows due to their rich tunability through structural control . By applying a colloidal approach, several structural features of the nanocrystals can be precisely controlled, including crystal phase, particle size, morphology, aliovalent dopant concentration, etc. At an atomic level, it was reported for WO 3– x bulk films and nanocrystals that the local structure of the Li insertion sites has an influence on their coloration efficiency and stability. ,, Moreover, it was shown that engineering the surface facets of WO 3– x nanocrystals by structural control can be used as a method to optimize several electrochromic properties .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, no significant change in the electrochromic spectral range was observed by engineering the Li insertion sites in these materials where a polaronic mechanism dominates. By contrast, in plasmonic transition metal oxide nanocrystals, nanocrystal shape has significant impact on the spectral range of electrochromic response in the nanocrystals. ,, During electrochemical reduction, the injected electrons accompanying Li insertion in metal oxides can be localized to a varying extent. In plasmonic metal oxides the added electrons tend to be delocalized, while in polaronic metal oxides they have been described as localized to a varying degree on the transition metal ions near the inserted Li.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochromism refers to an inimitable process involving reversible and persistent color change under a small electric field, which is attractive for information display. Compared with the emissive mode displays such as light-emitting diodes (LED) and liquid crystal displays (LCD), electrochromic displays with simple device structures do not need a continuous power supply to maintain the display content based on the memory effect. More importantly, with the high optical transparency in the bleached state, electrochromic displays can provide a “see-through” interface between humans and machines. Due to the remarkable features, many innovative research works on electrochromic displays have emerged in the past few years.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmonic semiconductor nanocrystals (PSNCs) have become an increasingly important area of research due to their advantages over traditional metallic plasmonic systems that include tunable carrier density via doping, complete transparency in the visible region, and their ability to strongly absorb near and mid-infrared (NIR, MIR) wavelengths. These unique properties have led to applications in the fields of sensing, electrochromics, and catalysis. For a typical plasmonic system, the plasma frequency ( ω p ) is primarily determined by the total number of free carriers ( n ) and the effective mass ( m* ) of these carriers, as illustrated by the Drude-Lorentz model, where e is the elementary charge of the free carrier and ε 0 is the permittivity of free space . For systems with the same concentration of aliovalent dopant ion, it is expected that the same number of free carriers would be generated.…”
Section: Introductionmentioning
confidence: 99%